Brand Image and Fashion Lifestyle Effects on Students’ Branded used Clothing Purchase Decisions - Fery Eko Putra; Buyung Romadhani; Nurinaya Nurinaya (Journal Social Society, 2026)
The urgency of this research lies in examining the influence of brand image and fashion lifestyle on students’ decisions to purchase branded second-hand clothing, given the growing popularity of sustainable consumption and fashion-conscious behavior among young consumers. This study aims to examine and analyze the effect of brand image and fashion lifestyle on students’ purchasing decisions of branded used clothing. The research employs a quantitative approach with a descriptive design. The population consists of students from the Faculty of Economics and Business, Universitas Muhammadiyah Makassar, who have purchased branded secondhand clothing, with a sample of 82 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis with SPSS. The results indicate that brand image has a positive and significant effect on purchasing decisions, as evidenced by a t-value of 6.472 and a significance level of 0.000 (< 0.05). Similarly, fashion lifestyle also shows a positive and significant influence, with a t-value of 2.141 and a significance level of 0.035 (< 0.05). Simultaneously, both variables significantly affect purchasing decisions, with an F-value of 59.579 greater than the F-table value of 3.08 and a significance level of < 0.001. The adjusted R-square value of 0.591 suggests that 59.1% of the variation in purchasing decisions can be explained by brand image and fashion lifestyle, while the remaining 40.9% is influenced by other factors outside the model. These findings highlight the importance of brand perception and lifestyle orientation in shaping consumer behavior toward branded secondhand clothing among students.